Pengaruh Skarifikasi Kimia Terhadap Perkecambahan Benih Jambu Mete (Anacardium occidentale L.) - Hartini Solle; Ira Y Dethan; Arnold Ch Hendrik (Saintek Lahan Kering, 2020)
Cashew is a plant that has the potential to help the welfare of farmers in the economic field. In general, cashew has a high economic value. Other benefits of cashew from the roots, stems and leaves can be used as medicine (Prihatman, 2000) and fruit and seeds to be a food source with high nutritional value.This study aims to determine the rate of cashew seed germination and optimum concentration by giving HCl and H2SO4. This research uses factorial pattern.The first factor is HCl with 4 levels of treatment consisting of 0%, 35%, 40%, 45% and 50%. The second factor is H2SO4 with 4 treatment levels consisting of 0%, 35%, 40%, 45% and 50%, and 4 controls.Each treatment consisted of 4 replications. Observation parameters in this study include germination, germination speed, and the average daily germination value. Empirical data obtained were analyzed using ANOVA (F test), followed by DMRT test at 5% level, if Fcount>Ftable (α=0.05). Based on ANOVA results, HCl administration significantly affected all observed parameters while H2SO4 and the interaction between HCl and H2SO4 did not significantly affect germination, germination speed and average daily germination value.DMRT test showed the fastest germination speed was found in the A4 treatment. The treatment with the highest value on the parameter observed was the average daily germination value in the A4 treatment. Thus it can be concluded that the HCl solution has a significant effect on each observation parameter. Whereas H2SO4 and the interaction between HCl and H2SO4 had no significant effect